2006
DOI: 10.1111/j.1467-9280.2006.01719.x
|View full text |Cite
|
Sign up to set email alerts
|

Shared System for Ordering Small and Large Numbers in Monkeys and Humans

Abstract: There is increasing evidence that animals share with adult humans and perhaps human infants a system for representing objective number as psychological magnitudes that are an analogue of the quantities they represent. Here we show that rhesus monkeys can extend a numerical rule learned with the values 1 through 9 to the values 10, 15, 20, and 30, which suggests that there is no upper limit on a monkey's numerical capacity. Instead, throughout the numerical range tested, both accuracy and latency in ordering tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
356
4
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 500 publications
(395 citation statements)
references
References 23 publications
25
356
4
3
Order By: Relevance
“…However, a wide range of non-human primate species certainly can deploy them for sets this size (Beran, 2007;Beran & Beran, 2004;Brannon & Terrace, 1998, 2000Call, 2000;Cantlon & Brannon, 2006, 2007Dehaene, 1997;Lewis, Jaffe, & Brannon, 2005). There were several significant differences between our study and these previous reports.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…However, a wide range of non-human primate species certainly can deploy them for sets this size (Beran, 2007;Beran & Beran, 2004;Brannon & Terrace, 1998, 2000Call, 2000;Cantlon & Brannon, 2006, 2007Dehaene, 1997;Lewis, Jaffe, & Brannon, 2005). There were several significant differences between our study and these previous reports.…”
Section: Discussioncontrasting
confidence: 63%
“…The ratio-limit signature of AM representations has been found in human adults, infants, rats, and various other species (Barth, Kanwisher, & Spelke, 2003;Brannon, Abbott, & Lutz, 2004;Brannon & Terrace, 1998;Brannon & Terrace, 2000;Cantlon & Brannon, 2006;Cordes, Gelman, & Gallistel, 2002;Gallistel, 1990;McCrink & Wynn, 2004;Platt & Johnson, 1971;Shettleworth, 1998;Whalen, Gallistel, & Gelman, 1999;Xu, 2003;Xu & Spelke, 2000;Xu, Spelke, & Goddard, 2005). Several studies document AM representations in rhesus monkeys (Brannon & Terrace, 1998, 2000Cantlon & Brannon, 2006;Flombaum, Junge, & Hauser, 2005). For example, looking-time studies reveal a capacity to discriminate 4 objects from 8, but a failure to discriminate comparisons where the ratio between sets is smaller, such as 4 vs. 6 (Flombaum et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, animals can discriminate between approximate numerosities via a system of analog magnitudes, in which performance is limited by the ratio between the quantities independent of absolute value. Cantlon and Brannon (2006), for example, demonstrated that in operantly trained rhesus monkeys, ratio determined numerical discrimination between quantities ranging from 1 to 30 items. Human infants and adults also represent large approximate numbers and show similar signature ratio limits (Barth et al 2003;Cantlon and Brannon 2006;Xu and Spelke 2000), suggesting a common system of numerical representation.…”
Section: Introductionmentioning
confidence: 99%
“…Wynn (1992) showed that infants look longer at a single doll that is revealed from behind an occluder when they previously observed an addition scenario (i.e., a second doll was added to an initial single doll, thus the expected solution would be ''two'') than when they previously observed a subtraction scenario (i.e., one doll was subtracted from a pair of dolls, thus the expected solution would be ''one''). Moreover, the time infants (and also monkeys) spend looking at visual arrays follows Weber's Law (Cantlon & Brannon, 2006;Libertus & Brannon, 2010). Furthermore, newborn infants preferentially look at arrays of visually presented objects that numerically match the number of auditory phonemes to which they have previously been familiarized (Izard, Sann, Spelke, & Streri, 2009).…”
Section: Development and Impairments Of Number Conceptsmentioning
confidence: 99%